2014
DOI: 10.17221/414/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid bacteria isolated from chicken carcasses with inhibitory activity against Salmonella spp. and Listeria monocytogenes

Abstract: Sakaridis I., Soultos N., Batzios Ch., Ambrosiadis I., Koidis P. (2014): Lactic acid bacteria isolated from chicken carcasses with inhibitory activity against Salmonella spp. and Listeria monocytogenes. Czech J. Food Sci., 32: 61-68.Lactic acid bacteria (LAB) isolated from poultry carcasses were added to BHI broth along with Salmonella spp. and Listeria monocytogenes in order to determine their antagonistic activity against the pathogens. There was a statistically significant reduction in Salmonella population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…It was revealed that the application of L. delbrueckii bacteria doesn't causes any changes in sensory characteristics of ground beef entire 10 days storage, moreover promote expanding of shelf-life due to inhibition of psychrophilic spoilage microorganisms which is in agreement with other authors [6,[24][25][26][27]. Thus, the LAB treated samples keep good quality for ten days whilst in the control sample at 7 day of storage appeared undesirable odor, greening and smooth on surface.…”
Section: Lab Inhibitory Effect On E Coli O157:h7 In Groundsupporting
confidence: 85%
“…It was revealed that the application of L. delbrueckii bacteria doesn't causes any changes in sensory characteristics of ground beef entire 10 days storage, moreover promote expanding of shelf-life due to inhibition of psychrophilic spoilage microorganisms which is in agreement with other authors [6,[24][25][26][27]. Thus, the LAB treated samples keep good quality for ten days whilst in the control sample at 7 day of storage appeared undesirable odor, greening and smooth on surface.…”
Section: Lab Inhibitory Effect On E Coli O157:h7 In Groundsupporting
confidence: 85%
“…It is a microbe that lives in the digestive tract of both humans and animals (Maragkoudakis et al 2009). L. salivarius isolated from chicken carcasses has the potential to be used as a preservative to increase safety and to extend the shelf life of chicken products (Sakaridis et al 2014). Bacteriosinogenic LAB has been shown to inhibit the growth of pathogenic and spoilage bacteria in meat (Gálvez et al 2008;Lücke 2000;Díaz-Ruiz et al 2012), including in sausage fermentation (Leroy et al 2006) and some food products (Bredholt et al 1999;Buchanan and Bagi 1997;Dimitrijevic´et al 1999;Duffes et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although the Salmonella count in T 1 , T 3 and T 4 was detectable but the levels recorded were significantly as low as 1.08, 0.5 and 0.41 log 10 cfu/g respectively. Earlier Sakaridis et al, (2014) reported a comparable inhibitory effect of Lactic acid bacterial on Salmonella count on fermented chicken carcass to nondetectable levels. Contrary to this El-Jalil et al, (2008) observed only a 50 per cent reduction in Salmonella count due to lactic acid fermentation of poultry manure waste.…”
Section: Resultsmentioning
confidence: 67%